St. Lucia : 2015 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
A moderate economic recovery is taking hold in St. Lucia. Favorable international conditions have contributed to improved demand for tourism, St. Lucia's main economic sector, and the external current account deficit has narrowed significantly. The authorities have made some progress in addressing a weak fiscal position. However, the financial sector continues to be impaired by nonperforming loans, public debt keeps rising, and unemployment remains very high, while external sector competitiveness continues to be weakened by an overvalued exchange rate, economies of scale disadvantages, and structural bottlenecks.